Cure characteristics and dielectric properties of magnetic composites containing strontium ferrite - Soloman, M. A.; Kurian, P.; Anantharaman, Maliemadom R.; Joy, Pattayil Alias (Journal of Elastomers and Plastics, 2005)
Hexagonal strontium ferrite (SrFe12O19) powders were synthesized by the conventional ceramic techniques. They were then characterized by the X-ray diffraction method and incorporated in the natural rubber matrix according to a specific recipe for various loadings of ferrite to produce rubber ferrite composites (RFCs). The processability of these compounds was determined by evaluating the cure characteristics namely, scorch time, cure time, minimum and maximum torque. The evaluation of the dielectric properties of ceramic strontium ferrite (SrF), natural rubber gum vulcanizate, and RFCs were done with the help of a Hewlett Packard (HP) impedance analyzer. The magnetic properties of these composites were studied using a Vibrating Sample Magnetometer (VSM). The effect of carbon black on the processability, and the magnetic and dielectric properties were also studied by the incorporation of carbon black into these composites. It has been found that the addition of these ferrites and carbon black does not affect the processability of these composites, whereas the physical properties are found to be modified. From the magnetic and dielectric measurements it has been found that flexible magnets having appropriate dielectric strength can be prepared by the incorporation of appropriate amount of SrF and carbon black in the natural rubber matrix.
Keywords: hexagonal ferrites; Magnetic materials; permanent magnets; rubber ferrite composites (RFCs); strontium ferrite